Genetic Variations and Frequencies of the Two Functional Single Nucleotide Polymorphisms of SLCO1B1 in the Thai Population - Na nakorn, Chalitpon; Waisayarat, Jariya; Dejthevaporn, Charungthai; Srisawasdi, Pornpen; Wongwaisayawan, Sansanee; Sukasem, Chonlaphat (Frontiers in Pharmacology, 2020)
Aim: To investigate the variations and the frequencies of SLCO1B1 gene in Thai population. Methods: Thai DNA samples were screened genotyping of c.388A>G and c.521T>C of the SLCO1B1 using TaqMan real-time PCR. The interpretations were categorized into five regions of Thailand. Results: The frequencies of two SNPs showed no significant in MAF among five regions, while the haplotypes of SLCO1B1*1a, *1b, *5, and *15 were 21.74, 65.39, 0.08 and 12.78%, respectively. The phenotypes of OATP1B1 transporter showed 75.85%, 22.57%, and 1.58% in normal, intermediate, and low function, which were in worldwide range. Conclusion: This study observed the variation of SLCO1B1 in Thai population that can represent the database on the function of the OATP1B1 transporter and the determination of clinical use of drugs.